An evaluation of influenza vaccine uptake in UK medical students - Gray, G; Cooper, J (Occupational medicine (Oxford), 2021)
The annual influenza vaccination is recommended for all front-line healthcare workers in the UK and is a crucial way of reducing mortality for vulnerable patient groups. However, to date the UK government has never explicitly monitored influenza vaccine uptake in medical students. This is important to ascertain, as students regularly move between clinical areas and are both a perfect vector for the spread of influenza and at an increased risk of contracting influenza themselves. This service evaluation was designed to evaluate the effectiveness of an influenza vaccination programme in one UK medical school and make recommendations to increase vaccination rates in the future. This service evaluation collected data about medical student uptake of influenza vaccination in one UK medical school. Two hundred and fifty-one students at different course stages completed questionnaires, answering questions on vaccination status and Likert-scale 'belief' questions to assess the subjective reasons behind vaccine refusal. There was a substantial difference between year group cohorts (~20%), with significantly higher vaccination rates in the preclinical year group. Two significant negative predictors of vaccination were found (P < 0.001), related to scepticism over the effectiveness of the vaccine and lack of convenient access to the vaccination. Results indicated that integrating information about the influenza vaccine into the curriculum would reduce lack of knowledge over the efficacy of the vaccine. The centralization of vaccination programmes at mandatory university-based learning events would mitigate against the problem of diversity of vaccination locations and lack of central accountability. The results of this service evaluation provide significant predictors of vaccination status for medical students and potential occupational health interventions to improve vaccine uptake in this group.